Enmity after the feud - Oman, Žiga (Acta Histriae, 2023)
Centring on non-nobles in the Duchies of Styria, Carniola and Carinthia, this paper addresses dispute settlement in Inner Austria, following the Imperial prohibition of feud in 1495 and the Habsburgs’ local consolidation of power earlier in the century. These developments are said to have brought about an end to feuding in the duchies in the 1500s, but by focusing on the concept of enmity, which articulated the same state of social relations, this article presents ample evidence that among all social classes dispute settlement retained much of the traditional practices well into the 1700s. Their survival was instrumentally underpinned by various courts of law and local authorities, regarding them as an indispensable element of keeping social cohesion and peace.
Keywords: fajda; Koroška; Kranjska; nasilje; ne zaključna dela; Notranja Avstrija; pomiritev; pravna kultura; reševanje sporov; sovražnost; Štajerska; zgodnji srednji vek